Managing major postpartum hemorrhage following acute uterine inversion in rural setting in Nepal: A case report - Sapkota, Bishal; Aryal, Divya; Bhandari, Jeetendra; Bhandari, Narendra (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Inversion of the uterus is a complication during the third stage of labor. Various factors have been associated with uterine inversion, though no obvious causes are found. Mismanagement of the third stage of labor is the leading cause. It must be diagnosed in the early stages to ensure proper treatment. In case of delayed diagnosis and reversal of the uterus, can lead to hypotension and difficulty in repositioning the uterus, which can result in death. Management of the patient with uterine inversion includes early diagnosis, maternal resuscitation to correct hypovolemia and shock, and uterine replacement. We report a 20-year-old primigravida case with acute uterine inversion during the third stage of labor at hospital setting in rural Nepal.